2008
DOI: 10.1080/09537100802220468
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid-induced platelet shape change revealed through LPA1–5receptor-selective probes and albumin

Abstract: Lysophosphatidic acid (LPA), a component of mildly-oxidized LDL and the lipid rich core of atherosclerotic plaques, elicits platelet activation. LPA is the ligand of G protein-coupled receptors (GPCR) of the EDG family (LPA 1-3 ) and the newly identified LPA 4-7 subcluster. LPA 4 , LPA 5 and LPA 7 increase cellular cAMP levels that would induce platelet inhibition rather than activation. In the present study we quantified the mRNA levels of the LPA 1-7 GPCR in human platelets and found a rank order LPA 4 =LPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 34 publications
0
44
3
Order By: Relevance
“…However, there are also discrepancies. Whereas albumin inhibits LPA-induced platelet activation, this effect is not observed in LPA 5 -transfected cells (28), and LPA does not elevate cAMP levels in platelets, which is observed in LPA 5 -transfected cells (18). These findings argue against the involvement of LPA 5 in platelet activation.…”
contrasting
confidence: 49%
See 4 more Smart Citations
“…However, there are also discrepancies. Whereas albumin inhibits LPA-induced platelet activation, this effect is not observed in LPA 5 -transfected cells (28), and LPA does not elevate cAMP levels in platelets, which is observed in LPA 5 -transfected cells (18). These findings argue against the involvement of LPA 5 in platelet activation.…”
contrasting
confidence: 49%
“…LPA 5 receptor mRNA is one of the most abundant LPA GPCR mRNAs in human platelets (28,30). Recently, we found that heterologously expressed LPA 5 showed similar SAR to that of platelets with preference to alkyl-glycerophosphate (AGP, also known as alkyl-LPA) over acyl-LPA (28). However, there are also discrepancies.…”
mentioning
confidence: 83%
See 3 more Smart Citations